Downside risk in commodity and equity markets - Pinho, Carlos (2019)
The aim of the present study is to analyse the tail risk of global commodities indices and a set of share indexes of several countries and regions. To measure the downside risk we use two tail risk measures, namely the Value-at-Risk (VaR) and the Conditional Value-at-Risk (CvaR), determined by parametric, semi-parametric and non-parametric approaches. Using daily prices comprising the period from January of 2002 to December 2016 and considering the pre- and post-global financial crisis sub-periods. A time-varying correlation between stock and commodity markets returns, comparing returns and downside risk measures was carry out. Overall, our findings indicate that tail risk of commodity markets is higher than stock market over the period, for almost all commodities, but that over the crisis period analysed the tail risk of stock market indices sharply increases to the same levels of commodities tail risk. The correlations between commodity and stock returns evolve through time. Considering the tail risk measures, for all analysed pairs, commodity and stock returns, we observe very high contemporaneous correlations during the crisis period.